A Model Framework for the Estimation of Animal ‘Suffering’: Its Use in Predicting and Retrospectively Assessing the Impact of Experiments on Animals - David B. Morton (Animals, 2023)
This paper presents and illustrates, with a working example, a hypothesis for the assessment of ongoing severity before and during an experiment that will enable humane endpoints and intervention points to be applied accurately and reproducibly, as well as helping to implement any national legal severity limits in subacute and chronic animal experiments, e.g., as specified by the competent authority. The underlying assumption of the model framework is that the degree of deviation from normality of specified measurable biological criteria will reflect the level of pain, suffering, distress and lasting harm incurred by or during an experiment. The choice of criteria will normally reflect the impact on an animal and have to be chosen by scientists and those caring for the animals. They will usually include measurements of good health such as temperature, body weight, body condition and behaviour, which vary according to the species, husbandry and experimental protocols and, in some species, unusual parameters such as time of the year (e.g., migrating birds). In animal research legislation, endpoints or severity limits may be specified so that individual animals do not suffer unnecessarily or endure severe pain and distress that is long-lasting (Directive 2010/63/EU, Art.15.2). In addition, the overall severity is estimated and classified as part of the harm: benefit licence assessment. I present a mathematical model to analyse the measurement data to determine the degree of harm (or severity) incurred. The results can be used to initiate alleviative treatment if required or if permitted during the course of an experiment. In addition, any animal determined to have breached the severity classification of a procedure can be humanely killed, treated or withdrawn from the experiment. The system incorporates the flexibility to be used in most animal research work by being tailored to the research, the procedures carried out and the species under investigation. The criteria used to score severity can also be used as additional scientific outcome criteria and for an analysis of the scientific integrity of the project.